Buccal hemineglect: is it useful to evaluate the differences between the two halves of the oral cavity for the multidisciplinary rehabilitative management of right brain stroke survivors? A cross-sectional study. Issue 3 (2nd April 2020) - de Sire, Alessandro; Baricich, Alessio; Ferrillo, Martina; Migliario, Mario; Cisari, Carlo; Invernizzi, Marco
ABSTRACT: Background : Unilateral spatial neglect (USN) is the most frequent cognitive impairment after right brain stroke, characterized by inattention to sensory stimuli in the opposite hemispace. It has been recently hypothesized a novel condition defined as "buccal hemineglect, " a particular form of USN with detrimental oral effects on right stroke survivors. Objective : The aim of our study was to compare the oral hygiene between the two halves of oral cavity in right stroke survivors. Methods : In this cross-sectional study, we assessed a cohort of right-handed subjects affected by right brain stroke with left hemiparesis, divided into two groups based on the presence of USN. We administered an evaluation protocol, including New Method of Plaque Scoring, Oral Hygiene Index (OHI), Gingival Index, Oral Food Debris Index, and Winkel Tongue Coating Index (WTCI). All outcome measures were assessed in the entire cohort considering both left and right halves of oral cavity. Results : Of the 21 patients included (mean aged 64.19 ± 7.60 years), the 14 affected by USN (mean aged 64.50 ± 8.06 years) had significantly worse values in all outcome measures in the left oral cavity compared to the right one ( P < .01). On the other hand, the seven patients not affected by USN (mean aged 63.57 ± 7.16 years) showed statistically significant differences only in OHI ( P = .03) and WTCI ( P = .03). Conclusion : Hygiene of left oral cavity was significantly worse than contralateral in right brain stroke survivors with USN. This study highlights the need to develop an adequate oral rehabilitation program in these patients.